Medico-social Profile of Women Experiencing Menopausal Syndrome Attending a Periurban Hospital - Tasnim, Saria; Hoque, FH Anamul; Nazmeen, Summyia (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Women’s health is a global concern now a days. Studies on issues relating to menopause is lacking Bangladesh and those been conducted mainly focus on physical and psychological symptoms around the time of menopause. This cross sectional study was done to explore the sociomedical context and nutritional characteristics of a group of women approaching menopause A total 106 women aged 45-60 years attending Gynae outpatient department of a tertiary hospital between March- May, 2013 was interviewed using structured questionnaire after obtaining informed written consent. Height and weight was measured using standardized procedure. Data analysed using SPSS. Mean age was 50.3± 5.3 years, about 75.5% were between 45-50 years, 85.1% had more than 2 children and 72.6% had history of Abortion. Mean age at menopause 44.65 ± 6.4 years, range 32-58 yrs. Mean BMI was 25± 4.2 and 43.4% were overweight or Obese. Chronic illness like hypertension and arthritis was present in (15.09%) and diabetes mellitus in 10.3% . The family relationship with children was good in 78.09%, husband was reported caring in 72.3% and 2.8% receive abusive behavior from husband. Only 8.5% were self earning, 24.5% and & 17.9% were dependent on children and husband respectively. With increasing life expectancy and improvements of health care services there is greater chance of survival for a women beyond menopause. Sociocultural and medical characteristics of midlife women is important to explore their specific health needs. Ensuring quality of life for this special group of women will help to better utilize their potential for development of the country. J Bangladesh Coll Phys Surg 2017; 35(4): 179-183